Long-Term Outcome of Children With Steroid-Resistant Nephrotic Syndrome: A Single Center Experience From Pakistan - Lubna Aman; Madiha Aziz; Noureen Akhter; Muhammed Mubarak; Ali Asghar Lanewala; Seema Hashmi (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the long-term outcome of children with steroid-resistant nephrotic syndrome at a single center in Pakistan. Study Design: Retrospective, observational study. Place and Duration of Study: Pediatric Nephrology Department, Sindh Institute of Urology and Transplantation, Karachi, Pakistan from July 2008 to June 2014. Methodology: The study included 153 children aged 4 months-12 years with steroid-resistant nephrotic syndrome. We collected data at the time of diagnosis and the last follow-up. The data was entered and analyzed by SPSS version 20. Results: Among 153 children, 84(55%) were males and 69(45%) females. At the time of diagnosis, 118(77%) were hypertensive and 65 (42.5%) had microscopic hematuria. Histopathological spectrum included focal segmental glomerulosclerosis, 63(41%); minimal change disease, 33(22%); IgM nephropathy, 9 (6%); mesangioproliferative glomerulonephritis, 26(17%), membranous glomerulonephritis, 13(8%) and membranoproliferative glomerulonephritis, 9(6%). Complete remission with cyclosporine was seen in 53(34.6%), partial remission in 36(23.5%), while 53(35%) developed chronic kidney disease, of which 26(78.8%) needed renal replacement therapy. Mortality was 21(13.7 %) and 11(7.2%) were lost to follow-up. Calcineurin inhibitors’ toxicity was seen in 52(34%). One patient received renal transplant but lost the graft 6 years post-transplant due to disease recurrence. Conclusion: Steroid-resistant nephrotic syndrome has significant long-term morbidity and mortality. Recurrence of disease in transplanted kidney is common and can result in graft loss.